Measuring ICD‐11 adjustment disorder: the development and initial validation of the International Adjustment Disorder Questionnaire. (3rd December 2019) - Shevlin, M.; Hyland, P.; Ben‐Ezra, M.; Karatzias, T.; Cloitre, M.; Vallières, F.; Bachem, R.; Maercker, A.
Abstract : Background: Adjustment disorder (AjD) is one of the most frequently used diagnoses in psychiatry but a diagnostic definition for AjD was only introduced in release of the ICD‐11. This study sought to develop and validate a new measure operationalizing the ICD‐11's narrative description of AjD, and to determine the current rate of people meeting the symptoms indicative of AjD in the general population of the Republic of Ireland. Methods: The International Adjustment Disorder Questionnaire (IADQ) was constructed to measure the core diagnostic criteria of ICD‐11 AjD: stressor exposure, preoccupations with, and failure to adapt to, the stressor, timing of symptom onset, and functional impairment. A nationally representative sample ( N = 1, 020) of adults from Ireland completed the IADQ. Results: Confirmatory factor analysis supported construct validity and the reliability estimates were excellent. The IADQ correlated strongly with depression, anxiety, and posttraumatic stress. The criteria were met by 7.0% of the sample, adjusted for other exclusionary disorders. Discussion: The IADQ is a measure based on the ICD‐11's description and produces reliable scores, however it should not be used for clinical assessment until validated with clinical interviews.